Manhaj Jamaluddin Al-Qasimi Dalam Penerapan Ilmu Al-Jarh Wa Al-Ta’dil - Moh. Saifuddin; Muhid; Andris Nurita (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract This article discusses Jamaluddin Al-Qasimi's thoughts or manhaj regarding the Science of Al-Jarh Wa Al-ta'dil in writing his book entitled Al-Jarh wa al-Ta'dil. The book by Al-Qasimi is used as a reference to find out the life history and quality of the narrators. Jamaluddin Al-Qasimi also took part in contributing to providing data on hadith narrators. From the book, it can be seen the comments of the hadith scholars who are critical of their opinion about the condition of each narrator, whether the narrator is accepted (maqbul) or rejected (mardud) so that later the status of hadith and the degree of hadith can be determined by the flow of transmission by the narrator. This article was reviewed using the library research method and also through the content analysis method approach. headlines from previous generations of critics. And after Jamaluddin Al-Qasimi compared his book with other critics' books of the same type, finally Jamaluddin Al-Qasimi's idealism in the book was not well connected between the concepts in the book and its reality. The source of the data for this article is in the form of documentation consisting of: The Book of History of Hadith Science, Introduction to Hadith Science, Mustalah al-Hadith Science, the book of al-Jarh wa al-Ta'dil, the collection of hadith 9 (pole al-tis'ah) and the sharh -his. The findings of this study are as follows: a). There are four schools of scholars in determining the quality of hadith, namely, mutasyaddid (strict-strict), muta'annut (excessive), mutawassit (moderate) and mutasahhil (soft-permissive). b). The implication of different schools of thought in determining the quality of hadith for the life of Muslims for the mutasyaddid (strict) school is that a hadith that does not meet the validity criteria cannot be used as proof of syar'iyyah. Likewise the mutawassit (moderate) schools of thought, unless there is another stronger argument (Qur'an-hadith) as its support. The muta'annut and mutasahhil schools of thought tend to use low-quality hadiths, especially for the virtues of charity and morality. Keywords: Jarh, Manhaj, Ta'dil, Hadith, Rawi.